Faktor-Faktor Yang Memengaruhi Minat Berinvestasi Dengan Ekspektasi Return Sebagai Variabel Moderasi - Awalina, Mei; Zein, Aliman Syahuri; Daulay, Putri Bunga Meiliana (Prodi Perbankan Syariah UIN Sumatera Utara Medan, 2025)
Investment is important in supporting the country's economic growth, economic growth is determined by savings and investment. If savings and investment are low, economic growth is also low. This research is motivated by the fact that the number of Foreign Investors (PMA) in Indonesia is always more than the number of Domestic Investors (PMDN). This means that people's interest in investing in Indonesia is still low compared to other countries. In this case, lecturers are considered to meet saving behavior, have knowledge about the importance of investment and money management. However, the reality is that there are still many lecturers who do not have investment and are not even interested in investing. Then, in previous research on investment interest, there were also inconsistencies in results. Thus, the purpose of this study is to find out the factors that affect investment interest with return expectations as a moderation variable. This study uses a quantitative approach with the Structural Equation Model (SEM) Method and the Partial Least Square (PLS) alternative. The data used are primary data obtained from questionnaires. The research population is lecturers of the Faculty of Islamic Economics and Business using a saturated sample of 52 people. The results of this study show that investment knowledge has a positive and significant effect on investment interest. Then, technological advances do not have a significant effect on investment interest. Furthermore, return expectations moderate the influence of investment knowledge on investment interest. Return expectations do not moderate the influence of technological advances on investment interest.